Konsumsi Makan dan Tingkat Pendapatan Keluarga dengan Kejadian Kekurangan Energi Kronik Pada Ibu Hamil di Wilayah Pesisir di Indonesia: Tinjauan Pustaka Sistematis: Food Consumption and Family Income Associated with Chronic Energy Deficiency in Pregnant Women in Coastal Areas of Indonesia: Systematic Review - Ningtyias, Farida Wahyu; Jamil, Alifia Istnaini; Antika , Ruli Bahyu (Universitas Airlangga, 2024)
Background: In Indonesia, Chronic Energy Deficiency (CED) is still a prevalent nutritional concern among pregnant women. CED is characterized by symptoms including anemia, bleeding, irregular maternal weight gain, and infection. CED in pregnant women is multifactorial, with food consumption intake serving as a direct contributor, and cultural factors as well as family income levels exert the indirect ones. Notably, pregnant women living in coastal areas tend to have low purchasing power, which in turn affects food intake and amplifies the risk of CED. Objectives: Analyzing the relationship between food consumption patterns and family income levels with the incidence of CED during pregnancy in coastal areas based on the results of other authors’ researches. Methods: This systematic review was carried out following the PRISMA guidelines to select and assess the quality of the articles. Data sources came from PubMed, DOAJ, Garuda Portal, Proquest, and Google Scholar from 2013-2022. The keywords used were